Consistent diel activity patterns of forest mammals among tropical regions - Vallejo-Vargas, A.F.; Sheil, D.; Semper-Pascual, A.; Beaudrot, L.; Ahumada, Jorge A.; Akampurira, E.; Bitariho, R.; Espinosa, S.; Estienne, V.; Jansen, P.A.; Kayijamahe, C.; Martin, E.H.; et al. (Springer, 2022)
An animal’s daily use of time (their “diel activity”) reflects their adaptations, requirements, and interactions, yet we know little about the underlying processes governing diel activity within and among communities. Here we examine whether community-level activity patterns differ among biogeographic regions, and explore the roles of top-down versus bottom-up processes and thermoregulatory constraints. Using data from systematic camera-trap networks in 16 protected forests across the tropics, we examine the relationships of mammals’ diel activity to body mass and trophic guild. Also, we assess the activity relationships within and among guilds. Apart from Neotropical insectivores, guilds exhibited consistent cross-regional activity in relation to body mass. Results indicate that thermoregulation constrains herbivore and insectivore activity (e.g., larger Afrotropical herbivores are ~7 times more likely to be nocturnal than smaller herbivores), while bottom-up processes constrain the activity of carnivores in relation to herbivores, and top-down processes constrain the activity of small omnivores and insectivores in relation to large carnivores’ activity. Overall, diel activity of tropical mammal communities appears shaped by similar processes and constraints among regions reflecting body mass and trophic guilds.